The Combination of Transformational Leadership and the MBKM Free-Form integrated Dormitory Program in Developing University Students’ Competence - Mas, Sitti Roskina; Suking, Arifin; Sulkifly, Sulkifly; Abdjul, Lilis (Jurnal Pedagogi dan Pembelajaran, 2025)
Research on transformational leadership in education still leaves several gaps, particularly regarding its effectiveness when integrated into dormitory-based programs that adopt a flexible curriculum combined with the Merdeka Belajar Kampus Merdeka (MBKM) framework. The challenge lies in how such a combination can systematically foster both hard and soft skills of university students in a holistic learning environment. This study aims to analyze the impact of transformational leadership combined with the MBKM Free Form-integrated dormitory program on student competency development. Using a quantitative descriptive design based on percentage analysis, the study involved 109 students as research subjects and employed a structured closed-ended questionnaire for data collection. The findings reveal that the program substantially enhances student competencies through role modeling, enthusiasm, encouragement of creativity, and opportunities for practice. Among the dimensions of transformational leadership, idealized influence emerged as the most influential factor, followed by inspirational motivation and intellectual stimulation, while individualized consideration showed relatively lower effectiveness. The study concludes that the integration of transformational leadership with MBKM Free Form dormitory programs provides a strategic pathway for developing students’ holistic competencies. The implications suggest that higher education institutions may adopt similar approaches to design effective programs that cultivate both academic and personal growth, thereby preparing students for dynamic future challenges.